Kedudukan Hak Asuh Anak Pasca Terjadinya Perceraian dari Istri yang Murtad Menurut Hukum Islam - Syaddan Dintara Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Provisions for Child Custody Based on the Compilation of Islamic Law are Muslim, mature, healthy in mind, trustworthy, single, able to educate children. rights and authority for those (women) who are apostates (non-Muslims) to take care of children. This study aims to find out more about child custody provisions based on Islamic law compilations and child custody due to divorce due to apostasy from a wife according to Islamic law compilations using normative methods that collect and analyze data in order to obtain a clear picture of the issues being discussed writing, with the aim of describing or describing the occurrence of a problem in a systematic, factual and also accurate manner and in order to get the truth in the process of perfecting this writing. KHI. Islamic law. Keywords: Child Custody, Divorce, Apostate Wives.